Education Level Predicts Retrospective Metamemory Accuracy in Healthy Aging and Alzheimer’s Disease - Szajer, Jacquelyn (2013)
The current study investigated the effect of education on retrospective metamemory accuracy in 143 healthy older adults and 143 early to moderate AD patients, using retrospective measures of confidence in the accuracy of retrieval responses in an episodic odor recognition memory task. Relative confidence accuracy was computed as the difference between confidence judgments for correct and incorrect responses. In both AD patients and controls, individuals reporting 17 years of education or more had significantly more accurate levels of confidence than individuals with 12 years or less. Thus, education was a significant predictor of retrospective metamemory accuracy in healthy aging and AD.